Application of Dynamic Controlled Atmosphere Technologies to Reduce Incidence of Physiological Disorders and Maintain Quality of ‘Granny Smith’ Apples - Tatenda Gift Kawhena; Olaniyi Amos Fawole; Umezuruike Linus Opara (Agriculture, 2021)
The efficacy of dynamic controlled atmosphere technologies; repeated low oxygen stress (RLOS) and dynamic controlled atmosphere-chlorophyll fluorescence (DCA-CF) to control superficial scald development on ‘Granny Smith’ apples during long-term storage was studied. Fruit were stored for 2, 4, 6, 8, and 10 months at 0 °C in DCA-CF (0.6% O2 and 0.8% CO2), regular atmosphere (RA)(≈21% O2 and 90–95% RH), and RLOS treatments: (1) 0.5% O2 for 10 d followed by ultra-low oxygen (ULO) (0.9% O2 and 0.8% CO2) for 21 d and 0.5% O2 for 7 d or (2) 0.5% O2 for 10 d followed by controlled atmosphere (CA) (1.5% O2 and 1% CO2) for 21 d and 0.5% O2 for 7 d. Development of superficial scald was inhibited for up to 10 months and 7 d shelf life (20 °C) under RLOS + ULO and DCA-CF treatments. Apples stored in RLOS + ULO, RLOS + CA, and DCA-CF had significantly (p < 0.05) higher flesh firmness and total soluble solids. The RLOS phases applied with CA or ULO and DCA-CF storage reduced the development of superficial scald by possibly suppressing the oxidation of volatiles implicated in superficial scald development.